2011
DOI: 10.1111/j.1471-0528.2011.03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrence and subsequent delivery after obstetric anal sphincter injuries

Abstract: Objective To investigate the recurrence risk, the likelihood of having further deliveries and mode of delivery after third to fourth degree obstetric anal sphincter injuries (OASIS).Design Population-based cohort study.Setting The Medical Birth Registry of Norway.Population A cohort of 828 864 mothers with singleton, vertexpresenting infants, weighing 500 g or more, during the period 1967-2004.Methods Comparison of women with and without a history of OASIS with respect to the occurrence of OASIS, subsequent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 28 publications
4
40
0
4
Order By: Relevance
“…For women who are symptomatic for urinary, flatus or faecal incontinence, or have findings that deviate from normal via manometric or endoanal ultrasonography associated with severe perineal trauma, it is suggested that an elective caesarean section should be recommended by the health care professional [3]. However, debate continues as to the most appropriate management of the subsequent mode of birth following severe perineal trauma, with discussions focussed around the protective mechanisms, potential morbidities and increased risk of subsequent perineal trauma associated with operative vaginal and vaginal births [3,18,20,21,26]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For women who are symptomatic for urinary, flatus or faecal incontinence, or have findings that deviate from normal via manometric or endoanal ultrasonography associated with severe perineal trauma, it is suggested that an elective caesarean section should be recommended by the health care professional [3]. However, debate continues as to the most appropriate management of the subsequent mode of birth following severe perineal trauma, with discussions focussed around the protective mechanisms, potential morbidities and increased risk of subsequent perineal trauma associated with operative vaginal and vaginal births [3,18,20,21,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Some women who experience severe perineal trauma express a preference for a vaginal birth subsequently, despite their fears regarding risk of recurrence [16]. There are contradictory findings reported in the literature regarding the risk of recurrence for women who have experienced third or fourth degree perineal trauma [18-21]. A review conducted by Edwards et al (2006) reviewed 271 cases, from 1991 to 2003, of women who experienced a subsequent labour and birth following severe perineal trauma with the first birth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe perineal trauma (SPT) is defined as a third degree tear, which involves injury to the perineum which extends to the anal sphincter complex; or a fourth degree tear, which involves injury to the perineum involving the external, internal and epithelium of the anal sphincter [3]. It is reported that internationally the incidence of SPT ranges from 05-10% [4,5]. While some women may experience no symptoms, other women may experience any or all symptoms including dyspareunia, stress or urge urinary incontinence, flatus and/or faecal incontinence, and are at risk of developing co-morbidities including pelvic organ prolapse and vesicovaginal fistulas [6-8].…”
Section: Introductionmentioning
confidence: 99%
“…In women who suffered OASIS at first birth, the incidence of a repeat OASIS has been shown to be 8.4% in hospital-based studies 2 and 7.2% in population-based studies 3 in the United Kingdom. In other countries, the rate of repeat OASIS in hospital-based and population-based studies has been reported to range widely from 2.0 to 7.2% 4,5 and from 5.6 to 7.1% 6,7 , respectively. Even though there are well defined risk factors for the occurrence of OASIS, such as nulliparity and instrument assistance at birth, the combination of these risk factors in different scoring systems does not allow the accurate prediction of OASIS 8 .…”
mentioning
confidence: 99%